The golden compass : the graphic novel, complete edition - Pullman, Philip, 1946- (His dark materials, 2017)
Lyra Belacqua is content to run wild among the scholars of Jordan College, with her dæmon familiar always by her side. But the arrival of her fearsome uncle, Lord Asriel, draws her to the heart of a terrible struggle -- a struggle born of Gobblers and stolen children, and a mysterious substance known as Dust. As she hurtles toward danger in the cold far North, Lyra never suspects the shocking truth: she alone is destined to win -- or to lose -- this more-than-mortal battle.